Fatigue of Electronic Materials 1994
DOI: 10.1520/stp23913s
|View full text |Cite
|
Sign up to set email alerts
|

Creep-Fatigue Damage Analysis of Solder Joints

Abstract: An anisotropic model of continuum damage mechanics has been developed to predict the creep-fatigue life of solder joints. With the help of the finite element method, the stress, strain, and damage fields of the time-dependent and temperature-dependent solder can be obtained. The main advantages of this model include: (1) It can predict the initial crack location and time and the subsequent crack growth paths; (2) The damage analysis is almost the same as in traditional viscoelastic finite element analysis; (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The FR4 board and BT interposer were modeled as temperature-dependent elastic and orthotropic. The time-independent behavior of the eutectic solder bumps was modeled temperature-dependent, multilinear elastic-plastic and the time-dependent behavior of the solder bumps was modeled using power-law/Arrhenius creep equation, [5], as (1) where is an experimentally determined constant equal to 1.84 10 (MPa) (s) is also experimentally determined to be 5.2, is the activation energy for creep which is 50 kJ/mol, is the universal gas constant equal to 8.314 10 kJ/mol-K, and is the temperature of the solder bumps in K.…”
Section: Materials Modelingmentioning
confidence: 99%
“…The FR4 board and BT interposer were modeled as temperature-dependent elastic and orthotropic. The time-independent behavior of the eutectic solder bumps was modeled temperature-dependent, multilinear elastic-plastic and the time-dependent behavior of the solder bumps was modeled using power-law/Arrhenius creep equation, [5], as (1) where is an experimentally determined constant equal to 1.84 10 (MPa) (s) is also experimentally determined to be 5.2, is the activation energy for creep which is 50 kJ/mol, is the universal gas constant equal to 8.314 10 kJ/mol-K, and is the temperature of the solder bumps in K.…”
Section: Materials Modelingmentioning
confidence: 99%
“…Therefore, in literature when modelling the mechanical behaviour of solder alloys, use is generally made of viscoplastic material models (Amagai, 1999;Basaran and Chanderoy, 2000). Numerous creep rate functions have been proposed, for which an extensive review can be found in Ju et al (1994). One of the commonly used viscoplastic models for solder alloys is the Anand model (Anand, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In this contribution the viscoplastic strain rate function defined by Perzyna (1966) is used to describe the time dependent mechanical behaviour (Sluis et al, 1999). In literature it is most commonly used to model secondary creep: Ju et al, 1994). Its parameters are more transparent than those of the Anand model and adaptation of the hardening law is straightforward, leading to a highly flexible model.…”
Section: Introductionmentioning
confidence: 99%
“…Very near the crack tip the stresses are dominated by the stress constant, b , which can be related to the stress intensity factor K ''' in (10). This equation is a little different from that of Reference 8, since b is one-half of the 1/(r constant term in Reference 8, and the K ''' is ( times of k in Reference 8.…”
Section: Formulation Of Mode-iii Displacement and Stress Fields Near mentioning
confidence: 97%